Efficacy and safety of remimazolam besylate in bronchoscopy for adults: A multicenter, randomized, double-blind, positive-controlled clinical study - Zhou, Ying-Yong; Yang, Shu-Ting; Duan, Kai-Ming; Bai, Zhi-Hong; Feng, Yun-Fei; Guo, Qu-Lian; Cheng, Zhi-Gang; Wu, Hui; Shangguan, Wang-Ning; Wu, Xiao-Min; Wang, Chun-Hui; Chai, Xiao-Qing; et al. (Frontiers in Pharmacology, 2022)
Background: With the development of fiberoptic bronchoscopy in the diagnosis and treatment of various pulmonary diseases, the anesthesia/sedation requirements are becoming more demanding, posing great challenges for patient safety while ensuring a smooth examination/surgery process. Remimazolam, a brand-new ultra-short-acting anesthetic, may compensate for the shortcomings of current anesthetic/sedation strategies in bronchoscopy. Methods: This study was a prospective, multicenter, randomized, double-blind, parallel positive controlled phase 3 clinical trial. Subjects were randomized to receive 0.2mg/kg remimazolam besylate or 2mg/kg propofol during bronchoscopy to evaluate the efficacy and safety of remimazolam. Results: A total of 154 subjects were successfully sedated in both the remimazolam group and the propofol group, with a success rate of 99.4%(95%CI of the adjusted difference -6.7×10-6% to -5.1×10-6%). The sedative effect of remimazolam was noninferior to that of propofol based on the prespecified noninferiority margin of -5%. Compared with the propofol group, the time of loss of consciousness in the remimazolam group (median 61 vs. 48s, P < 0.001), the time from the end of study drug administration to complete awakening (median 17.60 vs. 12.80min, P < 0.001), the time from the end of bronchoscopy to complete awakening (median 11.00 vs. 7.00min, P < 0.001), the time from the end of study drug administration to removal of monitoring (median 19.50 vs. 14.50min, P < 0.001), and the time from the end of bronchoscopy to removal of monitoring (median 12.70 vs. 8.60min, P < 0.001) were slightly longer. The incidence of Adverse Events in the remimazolam group and the propofol group (74.8% vs. 77.4%, P =0.59) was not statistically significant, and none of them had Serious Adverse Events. The incidence of hypotension (13.5% vs. 29.7%, P < 0.001), hypotension requiring treatment (1.9% vs. 7.7%, P=0.017), and injection pain (0.6% vs. 16.8%, P < 0.001) were significantly lower in the remimazolam group than in the propofol group. Conclusions: Moderate sedation with 0.2mg/kg remimazolam besylate is effective and safe during bronchoscopy. The incidence of hypotension and injection pain was less than with propofol, but the time to loss of consciousness and recovery were slightly longer.